Lutherʼs Anniversary (1717) and Conversion in the Saxon Electorʼs Court: starting points and possibilities of the research (Theatrum historiae, 2017)
The 200th Anniversary of Reformation, so called Lutherʼs Jubilee, in 1717, was in Saxony and also in the Holy Roman Empire connected with the conversion of the Electoral Prince Frederick Augustus (in spe Augustus III) to Catholicism. This change of the confession of the Wettinsʼ family (not only in the context of history of Protestants and also Catholics) has been interpreted by historians for a long time. And what kind of new historical methodology could be used for reinterpretation of this historical reality?
Keywords: Lutherʼs Anniversary 1717; Jubilee of the Reformation; Augustus the Strong (1670–1733); Frederick Augustus I (1670–1733; Frederick Augustus II (1696–1763); confession; conversion; Catholicism; Protestantism; Saxony; Holy Roman Empire; methodology